Spatial Battle: The Dynamics of Fisherman Community Resistance to the Management of the Lagoi International Tourism Area in Bintan Regency - Khairi Rahmi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
This article aims to discuss the phenomenon behind the management of the Lagoi International Tourism Area, which creates conflicts over the space for residential fishing communities and tourism space for foreign private parties. The presence of foreign private parties as a form of cooperation between the Indonesian government and the Singapore government has created resistance from the people who live as fishermen in struggle for their residential land (fishing ground). In addition, the area manager who came up with Singapore as a role model in managing the tourist area, which of course, there was not compatible with the socio-cultural conditions of the local community, participated in triggering rejection by the community. We uses the theory of resistance by James Scott regarding patterns and strategies of community resistance to fight for their residential land in the management of the Lagoi International tourist area. This research uses a case study research model, using participatory observation, in-depth interviews, and documentation as data collection techniques. The findings are that the fishing community's resistance towards the area manager experienced a shift from the previously closed symbolic pattern to an open-frontal pattern. Community resistance also experienced a weakening caused by external factors and internal factors.